Edible Connections: A Model for Citizen Dialogue Used to Discuss Local Food, Farm, and Community Issues - Joan S. Thomson; Jennifer L. Abel; Audrey N. Maretzki (Journal of Applied Communications, 2001)
Edible Connections: Changing the Way We Talk About Food, Farm, and Community introduces a model created to facilitate public dialogue on local food system issues such as farmland preservation, food safety, and hunger. Overall, this article describes and compares Edible Connections to other public discourse strategies used to engage individuals within a community in discussions regarding concerns about their local food system. Two characteristics set Edible Connections apart from other public dialogue strategies. First, the media—print, broadcast, e-commerce—are forum participants. Second is Edible Connections’ clear focus on food system issues. Its format allows those carrying out forums the flexibility to structure the dialogue to meet specific local objectives. Descriptions of how Pennsylvania communities defined and carried out Edible Connections to address locally important questions on the food system illustrate the ways in which Edible Connections helps to meet community interests and needs.